A quality of life study comparing scleral buckle and pneumatic retinopexy for the treatment of rhegmatogenous retinal detachment - Gauthier AC (Dove Medical Press, 2017)
Angela C Gauthier, Ron A Adelman Department of Ophthalmology and Visual Science, Yale School of Medicine, New Haven, CT, USAPatients who have undergone surgical treatment for retinal detachment may have significantly impaired visual-related quality of life.1 Although there are many studies that compare the visual outcomes and anatomical success of scleral buckle and pneumatic retinopexy in treating retinal detachment, there are inadequate data contrasting quality of life measures between these two approaches.2,3 A recent Cochrane review found that patients who underwent pneumatic retinopexy may be more likely to have recurrence of detachment but less likely to have choroidal detachment or a myopic shift than those who had scleral buckle.4 They concluded that there is still a dearth of important patient-centered information such as quality of life outcomes with these procedures.4 This study aimed to compare quality of life between patients who underwent scleral buckle or pneumatic retinopexy for treatment of rhegmatogenous retinal detachment.